2017
DOI: 10.18203/2394-6040.ijcmph20175770
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of intention to organ donation among general people in state of Puducherry: a cross sectional study

Abstract: Background: Organ transplantation is taken into account one among the best advances of contemporary science that has given several patients a revived lease of life. The target of study resolve the barrier and supporter of organ donation among general public, and to spot the factors that influence organ donation assent and rejection in state of Puducherry, India. Methods: A cross-sectional study had below soft on a sample of a hundred and fifty subjects handily. The eligible subjects were administered a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…15 Many students liked to be organ donor and were willing to motivate their family members and others to donate organs.in a study done by Arunachalam et al revealed same findings around 80.6% subjects has intention to donate their organs. 16 16% of the subjects were in favour of organ donation should be mandatory by law and the findings were similar to the study done in Kerala by Ali et al (15.2%). 17 In this study as to the willingness for the cadaveric donation only 17% participants responded positively and in the study by Aditya et al about 44.3% responded positively.…”
Section: Discussionsupporting
confidence: 88%
“…15 Many students liked to be organ donor and were willing to motivate their family members and others to donate organs.in a study done by Arunachalam et al revealed same findings around 80.6% subjects has intention to donate their organs. 16 16% of the subjects were in favour of organ donation should be mandatory by law and the findings were similar to the study done in Kerala by Ali et al (15.2%). 17 In this study as to the willingness for the cadaveric donation only 17% participants responded positively and in the study by Aditya et al about 44.3% responded positively.…”
Section: Discussionsupporting
confidence: 88%
“…Studies from different parts of the country have assessed knowledge and attitude toward organ donation using various domains. [ 7 8 9 10 ] However, we could not find any community-based study reporting adequacy of the knowledge regarding organ donation among general population. However, there were studies which reported adequacy of knowledge among health-care professionals such as doctors, nurses, undergraduate, and postgraduate medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Before discussing with their family members, they have the fear that their parents would not agree for it and this itself a major barrier to open their wish of going for it. 15 14% of the participants doesn't want to talk about death and information about their organ donation because of fear. 17% of the participants were frightened about the disfigurement and disabilities after the organ retrieval process.…”
Section: Discussionmentioning
confidence: 99%